"Call me comrade not mister": Vicente Rovetta and the spread of Maoism in Latin America's Global Sixties. Issue 2 (3rd July 2019) - Zhang, Kun; Xie, Xiaoxiao
ABSTRACT: The deterioration of Sino-Soviet relations in the late 1950s propelled the Chinese Communist Party (CCP) to take a greater interest in Latin America as part of the "Third World, " and the continent quickly became one of the key target areas of Chinese foreign propaganda activities. This essay introduces a relatively unknown figure in the existing historiography of the Latin American Left in the 1960s: Vicente Rovetta, who ran a bookshop in Montevideo called Nativa Libros (Native Bookshop). Through its successful cooperation with China International Bookstore (CIB) during the long Sixties, Nativa Libros contributed to the circulation of Maoist ideas in Uruguay and beyond. The story of Nativa Libros and its partnership with CIB illuminates a central characteristic of what Eric Zolov has called Latin America's "Global Sixties": the varied receptions of competing ideological projects in Cold War Latin America. The active role played by Rovetta as a local distributor for CIB testified to China's ambition to challenge the dominance of both the Soviet Union and the United States in Latin America, while also unveiling how Latin American leftists helped the "East Wind" to travel throughout the continent.